Ginkgo biloba extract EGb 761® improves cognition and overall condition after ischemic stroke: Results from a pilot randomized trial - Cui, Mei; You, Tongyao; Zhao, Yuwu; Liu, Ruozhuo; Guan, Yangtai; Liu, Jianren; Liu, Xueyuan; Wang, Xin; Dong, Qiang (Frontiers in Pharmacology, 2023)
Background: Patients who have had ischemic stroke are at risk for cognitive impairment. Quantified Ginkgo biloba extract EGb 761® has been used to treat cognitive dysfunction, functional impairment and neuropsychiatric symptoms in mild cognitive impairment and dementia. Objectives: To assess the cognitive-related effects of EGb 761® treatment in patients after acute ischemic stroke, as well as the feasibility of patient selection and outcome measures. Methods: We conducted a randomized, multicentric, open-label trial at 7 centers in China. Patients scoring 20 or lower on the National Institutes of Health Stroke Scale were enrolled between 7-14 days after stroke onset and randomly assigned to receive 240 mg per day of EGb 761® or no additional therapy for 24 weeks in a 1:1 ratio. Both groups received standard treatments for the prevention of recurrent stroke during the trial. General cognitive function and a battery of cognitive tests for sub-domains were evaluated at week 24. All patients were monitored for adverse events. Results: 201 patients ≥50 years old were included , with 100 assigned to the EGb 761® group and 101 to the reference group. The mean change from baseline on the global cognitive function as assessed by the Montreal Cognitive Assessment (MoCA) score was 2.92 in the EGb 761® group and 1.33 in the reference group (between-group difference: 1.59 points; 95% confidence interval [CI], 0.51 to 2.67; P< 0.005). For cognitive domains, EGb 761® showed greater effects on the Hopkins Verbal Learning Test Total Recall (EGb 761® change 1.40 vs. reference -0.49) and Form 1 of the Shape Trail Test (EGb 761® change -38.2 vs. reference -15.6). Potentially EGb 761®-related adverse events occurred in no more than 3% of patients. Conclusions: Over the 24-week period, EGb 761® treatment improved overall cognitive performance among patients with mild to moderate ischemic stroke. Moreover, our findings provide valuable recommendations for the design of future trials, including the criteria for patient selection. Clinical Trial Registration: www.isrctn.com, identifier ISRCTN11815543.